Participation in Christ: An Analysis of Pauline Soteriology - Aernie, Jeffrey W. (Horizons in biblical theology, 2015)
Paul’s conception and description of God’s soteriological enterprise continues to be a prominent focal point in constructions of the apostle’s theology. The present essay attempts to provide an outline of this aspect of Pauline theology from inception to corporate participation. The essay is comprised of three parts: (1) an extended examination of the definition of Paul’s gospel; (2) a brief analysis of the way in which the gospel relates to Paul’s own self-presentation; and (3) a few concluding thoughts concerning the way Paul extends his conception of the gospel to the ecclesial community. The primary argument of the essay develops a construction of the participatory nature of Pauline soteriology, building on the notion that the prophetic scope of Paul’s gospel compels the apostle to understand both his own ministry and Christian theology in terms of a participation in the new creation inaugurated within the Christ event.